Psychological Flourishing Among University Teachers - Laylan Azad Abdulaziz; Maha Hassan Bakir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The concept of psychological flourishing is one of the most important modern variables in positive psychology. These include positive feelings, mental integration, positive relationships, meaning of life, mental and social performance are among the signs of high mental health, as it keeps the individual away from mental disorders and has a high ability to survive with failures, psychological pressures and social problems. And he has the ability to understand himself, confidence in his abilities and the possibility of developing these capabilities according to the goals he is trying to achieve. For the purpose of achieving the objectives of the research, the researcher followed the descriptive approach because it is the most appropriate method between them in order to describe and analyze the phenomenon studied. The research statistical population consists of university teachers represented by the (scientific – humanistic) which number (2532) for academic year (2021 – 2022). A sample of the research consists from (253) university teachers which are divided into nine colleges (arts, engineering, language, agriculture, law, politics, education, shaqlawa education, management and economics). The researcher relied on collecting data from the research sample on the following: Adopting a scale (Ammar abdelamir al zawini, 2018) for psychological flourishing. The results were as follows: The research sample (university teachers) enjoys a high level of psychological flourishing. The high level of psychological flourishing for both sexes (male – female), and those with (scientific – humanistic) faculties, no difference according to the variable gender and faculties. The correlation of psychological flourishing with the scientific title in a positive and direct relationship. According to the results, the researcher reached a set of recommendations and suggestions.